2018
DOI: 10.1002/pssa.201800100
|View full text |Cite
|
Sign up to set email alerts
|

Pt‐Functionalized Nanoporous TiO2 Nanoparticles With Enhanced Gas Sensing Performances Toward Acetone

Abstract: A facile hydrothermal method is used to prepare Pt-functionalized nanoporous TiO 2 nanoparticles. These are used as gas-sensing material in sensors, fabricated according to the indirect heating method. Gas-sensing performance of the sensors is investigated by testing their gas response to acetone, which exhibits favorable selectivity, good gas response value, fast response/recovery time, low detection concentration and good long-term stability to acetone. Gas response β was defined as the ratio of R a /R g , w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The NMs, such as Ag, Au, Pd, Pt, and Rh NPs loaded/decorated onto the surfaces of semiconducting SnO 2 and TiO 2 enhance the gas sensing performance, due to the creation of new active centers on the MOx surface or changing the electronic structure of material (Epifani et al, 2012). As the alteration of electronic structure changes the electron accumulation due to the different work functions between NMs and semiconducting oxide (Chen et al, 2017), the chemical sensitization relies on effective catalytic properties of NMs (Xing et al, 2018).…”
Section: Nobel Metal Surface Loadingmentioning
confidence: 99%
“…The NMs, such as Ag, Au, Pd, Pt, and Rh NPs loaded/decorated onto the surfaces of semiconducting SnO 2 and TiO 2 enhance the gas sensing performance, due to the creation of new active centers on the MOx surface or changing the electronic structure of material (Epifani et al, 2012). As the alteration of electronic structure changes the electron accumulation due to the different work functions between NMs and semiconducting oxide (Chen et al, 2017), the chemical sensitization relies on effective catalytic properties of NMs (Xing et al, 2018).…”
Section: Nobel Metal Surface Loadingmentioning
confidence: 99%
“…Studies have revealed that doping TiO 2 with noble metals (e.g., Pt, Au, Pd, and Ag) or transition metals (e.g., Cu, and Zn) enhances the sensing characteristics, as they can regulate the morphology, enable surface reactions, transform the space charge distribution, and hence, advance the gas sensing characteristics. [5][6][7][8] Lupan et al [9] reported role of film thickness and surface functionalization using noble metals nanoclusters on the gas sensing performance of ultra-thin TiO 2 layers. Their TiO 2 ultra-thin films exhibited superior selectivity towards hydrogen gas, without being reliant on their thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Therefore, appropriate, and selective detection of BTEX vapours, predominantly at minimal concentrations, is very vital, efficient farming with capable conveyance and Page5 storage may be realized. Though several studies exist on the loading of noble metals on various SMOs [1,[6][7][8][9][10][11][12][13][14][15] , however, to the best of our information, no study has been conducted on the gas sensing properties of TiO 2 nanoparticles loaded with AgCu nanoparticles. In the current work, we show that a higher loading of both Ag/Cu switches the conductivity of TiO 2 from p-type to n-type, where such switching is not temperature or gas dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Pt in TiO 2 is also reported as a noble metal that favors the sensitivity of TiO 2 for the detection of other gases [99,100]. Xing et al [101] synthesized via hydrothermal method (5.67). The authors [101] attributed this better performance of the Pt/TiO 2 sensor to the catalytic effect of Pt, which increases the ability to absorb oxygen molecules and accelerate the reaction between adsorbed oxygen species (O x -) and acetone gas molecules, as well as the fact that Pt atoms introduce an intermediate energy level in the bandgap, making it easier for excited electrons to migrate from the valence band to conduction band.…”
Section: Tio 2 -Doping or Assistant Metalsmentioning
confidence: 99%
“…Xing et al [101] synthesized via hydrothermal method (5.67). The authors [101] attributed this better performance of the Pt/TiO 2 sensor to the catalytic effect of Pt, which increases the ability to absorb oxygen molecules and accelerate the reaction between adsorbed oxygen species (O x -) and acetone gas molecules, as well as the fact that Pt atoms introduce an intermediate energy level in the bandgap, making it easier for excited electrons to migrate from the valence band to conduction band. Abe et al [102] also reported that the introduction of Pt on the surface of TiO 2 favors the detection of gases (hydrogen, carbon monoxide).…”
Section: Tio 2 -Doping or Assistant Metalsmentioning
confidence: 99%